Attitude and determinants of contraceptive use among the Juang tribe: A cross-sectional study in Odisha, India - Prasanna Kumar Mudi; Manas Ranjan Pradhan (Elsevier, 2023)
Background: In India, Scheduled Tribes (STs) often have the lowest performance across various health measures, including contraceptive use. The condition of the Particularly Vulnerable Tribal Groups (PVTGs) is perceived to be worse. This study assesses attitudes and determinants of contraceptive use among the Juang tribe, a PVTG residing in Odisha, India. Methods: Data from a cross-sectional mixed-method research with a three-stage sampling design that was carried out in 2020-2021 were utilized for this study. The analysis was based on quantitative data from 360 currently married women aged 15-49 years, and qualitative interviews with women and men (12 Focus group discussions and 12 Key-Informant Interviews). Binary logistic regression was used to assess the determinants of contraceptive use among Juang women. Results: Two-thirds of Juang women had low/moderately favorable attitudes towards contraceptive method use. Thirty-four percent of women were using any contraceptive methods. The adjusted odds ratio (AOR) of using contraception was low among the women aged 15-24 years (AOR = 0.38; 95 % CI: 0.19-0.73), illiterate (AOR = 0.11; 95 % CI: 0.06-0.20), married below 18 years (AOR = 0.38; 95 % CI: 0.18-0.77), and not exposed to mass media (AOR = 0.34; 95 % CI: 0.18-0.65) than their respective counterparts. Conclusions: Among the Juang tribe, the use of contraception is limited and influenced by socio-cultural factors, including existing gender norms. Illiteracy, marriage below 18, younger age, and non-exposure to mass media are significantly associated with the non-use of contraception. Results suggest strengthening and expanding the family planning program outreach, especially among the young, illiterate Juang women.